Optimizing Planning Management in Jordan’s Construction Industry: Overcoming Challenges for Enhanced Performance - Alshamayleh, Hareth Zuhair; Amlus, Mohammad Harith Bin; Raje, Hasan Mohd Talat Ahmad Abu; Bataineh, Mohammad Jamal (Journal of Ecohumanism, 2024)
The construction industry in Jordan plays a critical role in the nation’s economic development. However, the sector faces numerous challenges, especially in terms of extended planning that lead to delays, cost overruns, and damage to the reputation of construction firms. This study focuses on the impact of the planning dimension on project performance within Jordan’s construction sector. Using the Resource-Based View (RBV) theory, the research emphasizes the strategic importance of internal resources, particularly skilled project managers and effective planning processes. The findings suggest that while detailed planning is essential for project success, external factors such as economic conditions and regulatory hurdles can undermine these efforts. The study highlights the need for comprehensive planning frameworks tailored to Jordan’s unique context. Recommendations include adopting robust planning strategies, investing in project management training, and enhancing stakeholder engagement to improve project outcomes and the competitiveness of Jordanian construction firms.